Viscoelastic and Fatigue Performance of Modified Bitumen Using Polymer and Bio-Based Additives: A Comparative Study - Ali Almusawi; Shvan Tahir Nasraldeen; Mustafa Albdairi; Hussein H Norri (Buildings, 2025)
This study investigates the performance and viscoelastic characteristics of unmodified and modified bitumen using Performance Grading, Frequency Sweep, and Linear Amplitude Sweep tests. The bitumen modifications include styrene-butadiene–styrene at 4% and 5%, animal bone powder at concentrations of 4%, 5%, and 6%, and waste cooking oil at 3%, 4%, and 5%. Performance Grading tests were conducted to evaluate the high-temperature performance of bitumen samples. Frequency Sweep tests were used to analyze the complex shear modulus and phase angle, providing insights into stiffness and elasticity. The Linear Amplitude Sweep tests assessed fatigue resistance by monitoring the degradation of the complex shear modulus under cyclic loading. Styrene-butadiene–styrene and animal bone powder significantly enhanced stiffness, elasticity, and fatigue resistance, with styrene-butadiene–styrene-modified samples achieving the highest performance grades and fatigue resistance. Waste cooking oil-modified bitumen reduces stiffness and fatigue resistance, indicating it primarily acts as a plasticizer. Styrene-butadiene–styrene and animal bone powder are effective modifiers for improving bitumen’s mechanical and fatigue properties and are suitable for demanding applications. In contrast, waste cooking oil compromises structural performance despite its environmental benefits, making it less suitable for high-performance use.